Financial Performance Evaluation of PT Sarimelati Kencana Tbk Using Profitability Ratios, Activity Ratios, and Solvency Ratios for the Period 2021-2023 - Dilla Shafia; Dianita Rezki Ayu; Erwin Budianto (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to assess the financial performance of PT Sarimelati Kencana Tbk from 2021 to 2023 using several types of financial ratio analysis. The financial ratios used are activity ratios (Total Asset Turnover), profitability ratios (Return on Assets), and solvency ratios (Debt to Asset Ratio). Pizza Hut Indonesia has a significant amount of fixed assets and outlets, making it important to determine whether these assets are being utilized productively through TATO analysis. Since PT Sarimelati Kencana experienced profit fluctuations (including losses in 2023), it is crucial to assess the effectiveness of managerial and operational strategies using ROA analysis, as ROA indicates how efficiently management utilizes assets to generate profits. Meanwhile, PT Sarimelati Kencana is also facing financial pressure marked by store closures and layoffs, so the DAR analysis can be used to measure the proportion of the company's assets financed by debt, whether the financing is healthy or overly reliant on debt. PT Sarimelati Kencana Tbk oversees the Pizza Hut franchise in Indonesia, which has faced significant challenges in recent years, including store closures and financial losses. The research methodology employed is descriptive quantitative, utilizing secondary data analysis obtained from the company's official financial statements. The findings indicate that the debt ratio is below industry norms, suggesting suboptimal asset utilization. The ROA ratio shows a declining trend to negative in 2023, reflecting a decline in profit. Meanwhile, the DAR ratio is very high and exceeds industry standards, indicating significant debt dependence and financial risk. These findings suggest the need for improved operational efficiency, reduced debt dependence, and strategies to improve the company's profitability. This study aims to serve as a reference for management decision-making and to enhance financial analysis studies in the Indonesian food and beverage industry.